Feasibility and Market Segmentation for Kanadevia’s LCCN (Waste-to-Steam) Integration in Indonesia - Hadikusuma, Alwin; Bima, Arya; Setiya, Yudhi; Sartini, Asrofah (Sekolah Tinggi Manajemen IPMI, 2025)
Indonesia faces rising energy costs, fossil fuel dependence, and a waste management crisis. The government has set a 23% renewable energy target by 2025 and promotes waste-to-energy (WtE) programs (Presidential Regulation No. 35/2018). This study examines the feasibility and market segmentation for Kanadevia’s LCCN (Low Carbon Circular Network) Waste to Steam technology integration in Indonesia. Leveraging strategic frameworks including PESTLE, SWOT, and Value Proposition Canvas, the research identifies significant opportunities for sustainable waste management and energy generation. Findings indicate a supportive policy environment in Indonesia, driven by renewable energy targets and impending landfill bans, creating favorable conditions for WtE adoption. The dairy processing manufacturing industry is identified as a primary target segment with potential expansion into industrial laundry, hospitals, and hospitality sectors. Key barriers include high upfront costs, feedstock supply inconsistencies, and the competitive advantage of subsidized coal. However, the prevailing waste crisis, increasing ESG compliance pressures, and rising energy costs present compelling opportunities. The study concludes that Kanadevia’s LCCN technology effectively addresses critical customer needs for cost-efficient, reliable, and environmentally compliant steam, offering substantial energy cost reductions and waste fee elimination. Strategic recommendations emphasize policy support, local partnerships, awareness campaigns, and tailored solutions to facilitate successful market integration.